A Meta-Analysis of the Efficacy of L-Carnitine/L-Acetyl-Carnitine or N-Acetyl-Cysteine in Men With Idiopathic Asthenozoospermia. Issue 2 (April 2021) - Wei, Guangzhu; Zhou, Zhongbao; Cui, Yuanshan; Huang, Yongjin; Wan, Zijin; Che, Xuanyan; Chai, Yumeng; Zhang, Yong
The meta-analysis was performed to access efficacy of L-carnitine/L-acetyl-carnitine (LC/LAC) and N-acetyl-cysteine (NAC) in men with idiopathic asthenozoospermia. We researched PubMed, EMBASE, and Cochrane Library databases and references to related articles. Finally, seven articles including 621 patients were analyzed. The results indicated that LC/LAC and NAC had a considerable improvement in sperm motility ( p = .03 and p < .0001, respectively) and normal morphology ( p = .006, p = .0002, respectively) compared with the placebo group. Besides, NAC had a significantly greater increase in sperm concentration ( p < .00001) and ejaculate volume ( p = .002) compared with the placebo group, and there was no significant difference in LC/LAC. For the analysis of serum hormones, NAC had no obvious differences in improving the serum testosterone, luteinizing hormone, follicle-stimulating hormone, and prolactin compared with non-treatment group. Conclusively, LC/LAC and NAC showed a greater improvement in sperm motility and normal morphology. Moreover, NAC has a positive effect on sperm concentration and ejaculate volume, whereas no obvious effect was observed in serum hormones.